The Double-Edged Sword of Notch Signaling in Cancer - South, Andrew P. (2012)
Recent deep sequencing of cancer genomes has produced an explosion of new data implicating Notch signaling in several human cancers. Unlike most other pathways, these data indicate that Notch signaling can be either oncogenic or tumor suppressive, depending on the cellular context. In some instances, these relationships were predicted from mouse models or presaged by developmental roles for Notch, but in other cases were unanticipated. This review discusses the pathogenic and translational significance of these new findings.